2013
DOI: 10.1007/s10397-013-0809-1
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of outpatient Thermachoice endometrial balloon ablation: a long-term 11-year outcome study

Abstract: The aim of this study was to evaluate the long-term treatment outcomes of outpatient Thermachoice balloon endometrial ablation under a direct local anaesthetic cervical block (LA-Thermachoice). This paper is a prospective cohort study and a postal questionnaire survey in a UK teaching hospital with the participation of 253 women with heavy menstrual bleeding (HMB) undergoing LA-Thermachoice over an 11-year period between 2001 and 2011. Treatment success was measured by postoperative bleeding patterns, improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Due to the fear of pain, the outpatient setting in ThermaChoice III has not been implemented in many hospitals. [13] Recently Kumar and Gupta demonstrated that ThermaChoice ablation was feasible in an outpatient setting using local anesthesia in a large cohort [14].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fear of pain, the outpatient setting in ThermaChoice III has not been implemented in many hospitals. [13] Recently Kumar and Gupta demonstrated that ThermaChoice ablation was feasible in an outpatient setting using local anesthesia in a large cohort [14].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13]19,20,26,35,37 Nine studies described the use of paracervical anaesthesia 17,18,22,23,27,28,31,32,36 and seven studies described the use of a combination of intracervical, paracervical and/or intrauterine anaesthesia. The ablation techniques that were used include thermal balloon endometrial ablation (TBEA), [11][12][13][17][18][19][20][21][22][23]25,27,[29][30][31]33,36 bipolar radiofrequency endometrial ablation (RFA), 19,20,22,28,32,34,37 hydrothermablation (HTA), 24,38 microwave endometrial ablation (MEA) 35 and hysteroscopic transcervical endometrial resection (T.C.R.E.). The ablation techniques that were used include thermal balloon endometrial ablation (TBEA), [11][12][13]…”
Section: Literature Searchmentioning
confidence: 99%
“…11,13,[17][18][19][20][21][22][23][24][25]27,[29][30][31][32][33][34]36,37 Seven of these articles reported a pain score measured during active ablation. These scores described the level of pain during active ablation and/or an 'overall' pain score of the procedure.…”
Section: Outcome Parametersmentioning
confidence: 99%
See 2 more Smart Citations